DAMPAK PROGRAM PENGELOLAAN SAMPAH BERBASIS MASYARAKAT SEBAGAI SALAH SATU PROGRAM CORPORATE SOCIAL RESPONSIBILITY BADAK LNG TERHADAP PEMBENTUKAN BUDAYA HIJAU (GREEN CULTURE) PADA MASYARAKAT KOTA BONTANG - Sunaryo, Busori; Susanti, Pratiwi Rini; Irkham, Agus M (METANA, 2013)
Abstract Bontang as a growing municipality continuously develops all aspects of life. One of negative effects of every developingÂ  city is the increase in the volume of its community waste. Until July 2011 the daily volume of Bontang waste is at average of 54,41 tonnes or 1.686,81 tonnes in July 2011. The waste issue mismanagement will potentially cause some decreases on the quality ofÂ  society health, environmental problems, and economy lost. Badak LNG as a key stakeholder of Bontang City was called to solve this waste management issue. In the frame of Corporate Social Responsibility-CSR program, Badak LNG created a special program which was called â€œA Society-based Plastic Managementâ€ as an alternative. It consists ofÂ  a series of programs such asÂ  waste bank, training for 3R (Reduce, Reuse, Recycle), repacking of carton waste for recycle, and small scale business of waste plastic chopping which now involves 13 groups consisting of 94 members. Based on the empirical study the writer has done, this â€œ Society-Based Plastic Managementâ€ has not only creates products (output) and outcome, but also has created a shared value of green culture towards Bontang community. Key words : Waste, CSR, Green Culture,Plastic chopping small scale business. Â